A Sociolinguistic Study of English Abbreviations Frequently Used by Gen Z on Tiktok - Laela Tusa’adah; Otong Setiawan Djauhari (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study explores the sociolinguistic functions of English abbreviations frequently used by Generation Z on TikTok. Using a qualitative descriptive approach, the research identifies 30 commonly used abbreviations and categorizes them according to their linguistic functions. The analysis reveals that these abbreviations serve expressive, interpersonal, informative, and contextual purposes. Their frequent use on TikTok reflects Gen Z’s unique digital identity and language practices shaped by social media culture. The study highlights the sociolinguistic significance of abbreviations as tools for identity performance, emotion expression, and community engagement in online communication. This study explores the sociolinguistic functions of English abbreviations frequently used by Generation Z on TikTok. Using a qualitative descriptive approach, the research identifies 30 commonly used abbreviations and categorizes them according to their linguistic functions. The analysis reveals that these abbreviations serve expressive, interpersonal, informative, and contextual purposes. Their frequent use on TikTok reflects Gen Z’s unique digital identity and language practices shaped by social media culture. The study highlights the sociolinguistic significance of abbreviations as tools for identity performance, emotion expression, and community engagement in online communication.